Reliability of rubrics in the assessment of orthodontic oral presentation - Naif A. Bindayel (Elsevier, 2017)
Aims: The aim of this study was to evaluate the reliability of using rubrics in dental education, specifically for undergraduate students' assessment in orthodontic oral presentation. Methods: A rubric-based case presentation assessment form was introduced to three contributing instructors. In each instructor's group, the course director, along with the assigned instructor, assessed 8 randomly selected fourth year male dental students utilizing the same assessment form (total of 24 students). The two final scorings made by the assigned instructor and the course director were then gathered for each student. The data of this prospective comparative study then was analyzed using paired t-test to look for any significant differences in the scoring of the course director and each instructor in each group. Results: No significant statistical differences were detected in grading variables between the instructors and the course director. Furthermore, the data showed no significant correlations between the students' final course grade, and their case presentation grades scored by instructors'/course director. Conclusion: Despite the elaborate nature of the routine orthodontic case presentation, the use of rubrics was found to be a promising reliable assessment element. Keywords: Assessment, Education, Orthodontic, Oral presentation, Reliability, Rubrics